What actually is social accountability? - Aston, Thomas (Medium, 2021)
Figuring out “what is the work?” we actually do sounds like a simple task, but in fact, it’s surprisingly difficult.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização

Accountability Ecosystems: The Evolution of a Keyword - Halloran, Brendan (Accountability Research Center, 2021)
Efforts to strengthen the accountability of the governing to the governed go back millennia. However, in the past decade there has been a renewed debate about how to advance public accountability. One domain where this conversation has taken place is that of efforts funded by donors (government development agencies and private philanthropies), primarily in the Global South and implemented by a set of national and international actors, including NGOs, private sector project implementors, and international institutions. Unfortunately, much donor-funded work has been underpinned by an understanding of accountability grounded in optimistic assumptions, particularly around the role of transparency and information technology. Early efforts by Rosie McGee and John Gaventa to take stock of this work highlighted the lack of theories of change grounded in a more nuanced, holistic and politically-informed understanding of accountability. Others began questioning the dominant ‘transparency + participation = accountability’ formulation that underpinned many projects; and most of them were just that, projects: start date, end date, work plan, logical framework, funding proposal, budget, etc. It was at the beginning of this discussion about what it takes to achieve real accountability that the term ‘Accountability Ecosystem’ started being used by a few individuals and organizations. The organization I worked for at the time, the Transparency and Accountability Initiative (TAI), had picked up the term, potentially from the organization I work for now, the International Budget Partnership (IBP).[i] I saw the term as a way to advance a more holistic and dynamic way to talk about the interaction of accountability actors, mechanisms and efforts in a given context, and a deliberate step away from more simplistic, linear formulations.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização

Social protection during conflict: reflections on Tigray - Sabates-Wheeler, Rachel; Lind, Jeremy (Institute of Development Studies, 2021)
Conflict and an ensuing humanitarian crisis in Ethiopia’s northern Tigray region have led to substantial population displacement and threaten the lives and livelihoods of millions. In a situation where rising needs outstripped preliminary humanitarian responses and where safety net programmes that were purposed for shock-response have been curtailed or stopped functioning altogether, what are the […]
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; Social Protection PEA; conflict / conflito; social protection / proteção social

Conflict is the new ‘hazard’ on the social protection block - Sabates-Wheeler, Rachel; Slater, Rachel; Lind, Jeremy; Harvey, Paul; Oosterhoff, Pauline; Faith, Becky; Naess, Lars Otto; Selby, Jan; Roberts, Tony; Longhurst, Daniel; Rohwerder, Brigitte; Collyer, Michael; et al. (Institute of Development Studies, 2021)
Although social protection has the potential to address crises in different ways, the evidence base is thematically and geographically patchy. The Foreign, Commonwealth and Development Office-funded (FCDO)-funded Better Assistance in Crises (BASIC) Research programme aims to inform policy and programming on effective social assistance in situations of crisis, including those experiencing climate-related shocks and stressors, protracted conflict and forced displacement.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Social Protection PEA; conflict / conflito; social protection / proteção social

All hands on deck: Harnessing accountability through external public audits | Publications (International Budget Partnership)
This report is the first ever comprehensive look at the strength of audit and oversight systems globally and comes at a time when supreme audit institutions (SAIs) are under enormous pressure to ensure governments are effective stewards of COVID-19 emergency spending in ways that advance the public interest and protect development progress.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização